The changing discourse of city plans: Rationalities of planning in Perth, 1955-2010 - MacCallum, Diana; Hopkins, D. (Routledge, Taylor and Francis Ltd, 2011)
Plans are among the most durable products of planning, and as such offer a revealing window into the worlds of the planners of their time. In this paper we set out a methodology for viewing those worlds using critical discourse analysis (CDA). This method focuses on four key textural features of plans: construal of substance, construction of agency, generic structure, and presentation. Together they enable the investigator to go beyond thematic discourses and uncover the institutional, political and ideological role of planning during the time period in which plans are produced. We use this method to interrogate the changing rationalities governing planning in Western Australia (WA) since the Second World War by analysing the four major city plans for Perth, covering a period from 1955 to 2010. This longitudinal analysis suggests that planning in WA mirrors concurrent trends in international planning theory, and highlights the significance of "the plan" as an object of inquiry for revealing the changing nature of planning and planners over time.